1992
DOI: 10.1210/jcem.75.2.1639948
|View full text |Cite
|
Sign up to set email alerts
|

Induction of azoospermia in normal men with combined Nal-Glu gonadotropin-releasing hormone antagonist and testosterone enanthate.

Abstract: The effects of a combined GnRH antagonist and testosterone (T) replacement regimen on gonadotropins and spermatogenesis were examined to assess its potential as a male contraceptive regimen. The potent Nal-Glu GnRH antagonist ([Ac-D2-Nal1,D4-Cl-Phe2,D3-Pal3,Arg5, D4-p-methoxybenzoyl-2-amino butyric acid6,D-Ala10]GnRH) was administered daily (7.5 mg, sc) to eight normal men for 16 weeks. T enanthate was given im starting at week 2 and every 2 weeks thereafter through week 14 of the treatment phase. Serum LH, FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 27 publications
0
13
0
3
Order By: Relevance
“…Previously, it was believed that the development of the GnRH antagonist depot preparation is impracticable, as only GnRH antagonist doses of 7.5-20 mg/day effectively suppressed gonadotropins as well as sex hormones, whereas lower doses were ineffective (3)(4)(5)9). However, this study demonstrates that after an effective loading dose period, much smaller doses of the GnRH antagonist are sufficient.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Previously, it was believed that the development of the GnRH antagonist depot preparation is impracticable, as only GnRH antagonist doses of 7.5-20 mg/day effectively suppressed gonadotropins as well as sex hormones, whereas lower doses were ineffective (3)(4)(5)9). However, this study demonstrates that after an effective loading dose period, much smaller doses of the GnRH antagonist are sufficient.…”
Section: Discussionmentioning
confidence: 63%
“…However, we could show that GnRH agonists are not suited for male contraception because they do not cause a prolonged and effective FSH decrease and thus fail to suppress spermatogenesis in male volunteers (2). In contrast, the GnRH antagonist Nal-Glu given at relatively high doses of 7.5-20 mg/day caused a significant suppression of both gonadotropins and spermatogenesis (3)(4)(5). However, high daily doses of the GnRH antagonist Nal-Glu, which can result in local adverse side-effects, are impractical and too expensive for long term use.…”
mentioning
confidence: 98%
“…Initial very small trials investigated the GnRH antagonist Nal-Glu, administered by daily sc injection, in combination with testosterone to maintain peripheral androgenicity. In the first two trials, 14 of 16 subjects achieved azoospermia by 6 -10 wk of treatment (258,259). But a third small, randomized trial demonstrated no difference in azoospermia with TE plus Nal-Glu compared with TE alone, at least at the doses given (260).…”
Section: Adding Gnrh Analogs To Hormonal Contraceptive Regimensmentioning
confidence: 99%
“…Several studies dating back to the early 1990s [88][89][90][91][92] suggest a rapid onset of suppression of spermatogenesis to azoospermia. This group of studies, each with small populations, suggested a good response to this combined therapy.…”
Section: Testosterone and Gnrh Analogues (Agonists And Antagonists)mentioning
confidence: 99%